Validation of Diagnostic and Performance Characteristics of the Wireless Motility Capsule in Patients With Suspected Gastroparesis - Lee, Allen A. (Clin Gastroenterol Hepatol, 2018)
BACKGROUND & AIMS: It is a challenge to make a diagnosis of gastroparesis. There is good agreement in results from wireless motility capsule (WMC) analysis and gastric emptying scintigraphy (GES), but the diagnostic yield of WMC is unclear and the accuracy of this method has not been validated. We compared the performance characteristics of WMC vs GES in assessing gastric emptying in patients with suspected gastroparesis. METHODS: We performed a prospective study of 167 subjects with gastroparesis (53 with diabetes and 114 without) at 10 centers, from 2013 through 2016. Subjects were assessed simultaneously by GES and with a WMC to measure gastric emptying and regional transit. Delayed gastric emptying by GES was defined as more than 10% meal retention at 4 hrs whereas delayed gastric emptying by WMC was defined as more than 5 hrs for passage of the capsule into the duodenum; a severe delay in gastric emptying was defined as a gastric emptying time of more than 12 hrs by WMC or more than 35% retention at 4 hrs by GES. Rapid gastric emptying was defined as less than 38% meal retention at 1 hr based on by GES or gastric emptying times less than 1:45 hrs by WMC. We compared diagnostic and performance characteristics of GES vs WMC. RESULTS: Delayed gastric emptying was detected in a higher proportion of subjects by WMC (34.6%) than by than GES (24.5%) (P=.009). Overall agreement in results between methods was 75.7% (kappa=0.42). In subjects without diabetes, the WMC detected a higher proportion of subjects with delayed gastric emptying (33.3%) than GES (17.1%) (P<.001). A higher proportion of subjects with diabetes had delayed gastric emptying detected by GES (41.7%) than by WMC (17.1%) (P=.002). Severe delays in gastric emptying were observed in a higher proportion of subjects by WMC (13.8%) than by GES (6.9%) (P=.02). Rapid gastric emptying was detected in a higher proportion of subjects by GES (13.8%) than by WMC (3.3%) (P<.001). Regional and generalized transit abnormalities were observed in 61.8% subjects and only detected by WMC. CONCLUSION: Although there is agreement in analysis of gastric emptying by GES vs WMC, WMC provides higher diagnostic yield than GES. WMC detects delayed gastric emptying more frequently than GES and identifies extra-gastric transit abnormalities. Diabetic vs non-diabetic subjects have different results from GES vs WMC. These findings could affect management of patients with suspected gastroparesis. ClinicalTrials.gov no: NCT02022826.